1993
DOI: 10.1021/bi00054a009
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli fumarase A catalyzes the isomerization of enol and keto oxalacetic acid

Abstract: Fumarase A, a product of the fumA gene of Escherichia coli, has been found to catalyze the isomerization of enol to keto oxalacetic acid (OAA) in addition to catalyzing the fumarase reaction. The kcat/Km for the isomerization is almost identical to that for the fumarase reaction. The isomerization reaction apparently takes place at the same active site as the fumarase reaction since both reactions show a similar sensitivity to inactivation by O2, both reactions are strongly inhibited by 2-hydroxy-3-nitropropio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Proteins with OAA enol‐keto tautomerase (OAT, EC 5.3.2.2) activity from several prokaryotes and eukaryotes have been reported [58,61,62]. It was demonstrated that OAT enzymes, in the presence of a (keto) OAA‐metabolizing enzyme, protect SDH from enol‐OAA inactivation that would otherwise occur as a result of promiscuous malate oxidation [56].…”
Section: Promiscuous Succinic Dehydrogenase Activity Results In Enol‐mentioning
confidence: 99%
See 3 more Smart Citations
“…Proteins with OAA enol‐keto tautomerase (OAT, EC 5.3.2.2) activity from several prokaryotes and eukaryotes have been reported [58,61,62]. It was demonstrated that OAT enzymes, in the presence of a (keto) OAA‐metabolizing enzyme, protect SDH from enol‐OAA inactivation that would otherwise occur as a result of promiscuous malate oxidation [56].…”
Section: Promiscuous Succinic Dehydrogenase Activity Results In Enol‐mentioning
confidence: 99%
“…It was demonstrated that OAT enzymes, in the presence of a (keto) OAA‐metabolizing enzyme, protect SDH from enol‐OAA inactivation that would otherwise occur as a result of promiscuous malate oxidation [56]. Interestingly, in mammals, the TCA cycle hydro‐lyase enzyme aconitase has OAT activity [63], while in E. coli , another TCA cycle hydro‐lyase enzyme fumarate hydratase (FH) has OAT activity [62]. For both enzymes, OAT activity is catalyzed with nearly the same catalytic efficiency as their respective hydro‐lyase activities [62].…”
Section: Promiscuous Succinic Dehydrogenase Activity Results In Enol‐mentioning
confidence: 99%
See 2 more Smart Citations
“…No deuterium was present in the (S)-malate or fumaric acid in the reaction mixtures incubated with fumarase A or fumarase C, while the deuterium was still present in the (S)-malate in the fraction to which no enzyme was added. Since fumarase C is known to specifically eliminate water from (S)-malate in anti-fashion (Scheme 6, red box) (Gawron and Fondy, 1959;Flint, 1993) and the stereochemical course for fumarase A was identical it also had to be anti. Thus both fumarases catalyse the anti-addition of water to fumaric acid to form (S)-malate (Englard, 1960;Gawron et al, 1961;Karsna, 1958).…”
Section: Classification Of Hydratasesmentioning
confidence: 99%